Depolymerization of cellulose to glucose by oxidation–hydrolysis. Issue 3 (16th December 2014) - Zhou, Lipeng; Yang, Xiaomei; Xu, Jiaolong; Shi, Meiting; Wang, Feng; Chen, Chen; Xu, Jie
Abstract : An oxidation–hydrolysis strategy was developed for depolymerization of cellulose. The method needs no additional catalyst. Part of the hydroxymethyl groups on glucose units were oxidized to carboxyl groups during the preoxidation treatment, and the generated acid sites act as the catalytic active centers for the following depolymerization of cellulose. Abstract : An oxidation–hydrolysis strategy was developed for depolymerization of cellulose. Part of the hydroxymethyl groups on glucose units were oxidized to carboxyl groups during the preoxidation treatment, and the generated acid sites act as the catalytic active centers for the following depolymerization of cellulose. After α-cellulose was pretreated by air at 210 °C for 48 h, 23.3% yield of glucose was obtained in water at 150 °C for 8 h without additional catalyst. The ratio of cellulose/water has no obvious influence on the yield of glucose. 17.9% yield of glucose for α-cellulose can still be obtained even at the weight ratio of 0.4, where up to 75 g L −1 of glucose solution is obtained. For microcrystalline cellulose, 25.2% yield of glucose was obtained for hydrolysis at 170 °C for 8 h. It was revealed that the generated carboxyl acid groups in the oxidation step are the catalytic sites for the hydrolysis of cellulose.